PKM Sosialisasi Integrasi Solidaritas Dalam Organisasi Kemahasiswaan - Yusuarsono, Yusuarsono; Lorita, Evi; Sariningsih, Marida; Saputra, Harius Eko; Rikardo, Yanuar; Sahara, Sherly Marta (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This Community Service (PKM) activity aims to foster and strengthen the value of social solidarity in student organizations, especially the Public Administration Student Association (HIMAPLIK) of Dehasen University, Bengkulu. In the era of globalization that is full of challenges of individualism and rapid social change, the millennial generation as part of the academic community needs to have a high collective awareness and spirit of togetherness to maintain the integrity of the organization. This activity was carried out in the form of a Public Dialogue with the theme